2021
DOI: 10.3390/molecules26123674
|View full text |Cite
|
Sign up to set email alerts
|

Cheminformatic Profiling and Hit Prioritization of Natural Products with Activities against Methicillin-Resistant Staphylococcus aureus (MRSA)

Abstract: Several natural products (NPs) have displayed varying in vitro activities against methicillin-resistant Staphylococcus aureus (MRSA). However, few of these compounds have not been developed into potential antimicrobial drug candidates. This may be due to the high cost and tedious and time-consuming process of conducting the necessary preclinical tests on these compounds. In this study, cheminformatic profiling was performed on 111 anti-MRSA NPs (AMNPs), using a few orally administered conventional drugs for MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…Lipinski’s rule of five, referred to as Pfizer’s rule, is one of the techniques used to evaluate the drug-likeness of a chemical compound as it delineates the relationship between pharmacokinetics and physicochemical parameters. It determines the potential of the biological activities or pharmacological properties of a chemical compound and its effectiveness as an oral drug in humans [ 39 , 40 ]. We adhered to compounds with no violations or a minimum of a single violation, as violations of two or more indicate that drug candidates may not be orally active [ 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Lipinski’s rule of five, referred to as Pfizer’s rule, is one of the techniques used to evaluate the drug-likeness of a chemical compound as it delineates the relationship between pharmacokinetics and physicochemical parameters. It determines the potential of the biological activities or pharmacological properties of a chemical compound and its effectiveness as an oral drug in humans [ 39 , 40 ]. We adhered to compounds with no violations or a minimum of a single violation, as violations of two or more indicate that drug candidates may not be orally active [ 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…It determines the potential of the biological activities or pharmacological properties of a chemical compound and its effectiveness as an oral drug in humans [ 39 , 40 ]. We adhered to compounds with no violations or a minimum of a single violation, as violations of two or more indicate that drug candidates may not be orally active [ 40 , 41 ]. Hence, compounds with predicted poor oral absorption but high potency, as revealed in the Supplementary Materials , could be improved upon using an optimized absorption enhancement approach in future research.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The identification of compounds that can target different stages of the biosynthesis of peptidoglycan cell wall may result in the 22 To update the data set, a further literature search, using the same keywords and search strategies described in the study was used to identify other recent studies that reported natural products with activities against MRSA. 22 In all, a sum of 262 anti-MRSA natural products (AMNPs) sourced from plants, marine organisms and microorganisms was used in this study. The Simplified Molecular Input Line Entry System (SMILES) structures of the AMNPs and their respective bioactivity data were retrieved and stored as text files (Table S1).…”
Section: Introductionmentioning
confidence: 99%